Penerapan Metode Weighted Product dalam Penyeleksian Supervisor Terbaik - Adrianus Gultom; Titus Kristanto; Yonky Pernando; Joko Kuswanto; Nursaka Putra; Amsar Amsar (Bulletin of Informatics and Data Science, 2023)
In this study, the authors used the Weighted Product (WP) method to select the best supervisor at PT PLN (Persero). The Weighted Product (WP) method is the most appropriate method to be used in the selection stage for candidates with the potential to be the best supervisors. In applying the WP (Weighted Product) method, managers can rank by looking for the weight value of each attribute. The results of the study stated that alternative A2 had the best value with a value of 0.11877